The Effect of Digital Marketing Strategy on Increasing Interest of New Students: A Case at Vocational High School in Sidoarjo - Zhafran, Ahmad (LP. Ma'arif Janggan Magetan, 2024)
Vocational High Schools (SMKs) in Indonesia, including SMK Darma Siswa 1 Sidoarjo, face significant challenges in increasing student enrollment amid intense educational competition. This research aims to analyze the impact of digital marketing strategies on increasing interest from prospective students. Using a mixed-methods approach, data were collected through surveys of 120 students and parents, interviews with five school marketing personnel, and content analysis of the school's official website and social media platforms. The results show that 75% of respondents acknowledged the importance of digital marketing content especially visual materials and alums testimonials, in increasing their understanding and interest. Instagram and Facebook were the most effective platforms, supported by the school's website. However, digital efforts are still lagging behind traditional brochure distribution in terms of enrollment conversion. This study recommends improving digital outreach quality, increasing social media engagement, and leveraging alums as brand ambassadors to strengthen recruitment.